The phenomenon of «culture shoots» and the problem of resistance to the culture (Journal of Philosophy Culture and Political Science, 2018)
This article deals with the problem of cultural integration of migrants. The authors of the article note that the cultural adaptation of migrants largely depends on the degree of similarity and differences incultures. Racial, linguistic, religious intimacy promotes more rapid adaptation, and vice versa. Successfulcultural adaptation of migrants, according to the authors, is possible in the presence of intercultural competence,which can become a solid basis for intercultural dialogue. The heterogeneity of modern society,combined with global interdependence, requires people to have certain, knowledge, skills and skills inintercultural communication (intercultural competence). The formation of intercultural competences ina person promotes the establishment of a dialogue in a multicultural society that plays an important rolein the process of learning cohabitation in the conditions of growing globalization and, thus, contributingto the reduction of the risks of conflicts and cultural fragmentation of society. The consequence of a“cultural shock” is often cultural marginalization, which can grow into a misunderstanding of people ofother cultures, their opposition. European governments have attempted to successfully integrate Muslimmigrants into the European socio-cultural environment. Cultural integration, according to a number ofpolitical leaders of the European Union, will allow Muslim migrants, if not completely Europeans, thenat least European Muslims, therefore, there is quite a strong pressure on Muslims to move towards theliberalization of Islam, an example of which can be the largest European project – Euroislam. EuropeanIslam or Euro-Islam – is a new direction of Islam emerging in Europe, within the liberalization of Muslimsociety. The new kind should combine the principles of Islam with the cultural values of Europe, suchas democracy, the rule of law, human rights, gender equality, which will allow Muslims to considerthemselves full citizens of Europe on the one hand, and reduce the level of cultural differences betweenChristians and Muslims. The idea of Euroislam is severely criticized by the conservative clergy of Iran andSaudi Arabia, who see liberalization of Islam as an attempt to dissolve it in the general cultural values ofEuropean society.Key words: “Cultural shock”, intercultural competence, opposition of cultures.